Interferensi dalam Dialog Film Rudy Habibie Sutradara Hanung Bramantyo - Apriliani, Dewi; Herwandi, Herwandi (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
This research aims to describe and analyze interference at the phonological and morphological levels in the dialogues of the movie "Rudy Habibie," directed by Hanung Bramantyo. The method employed in this study is descriptive research with a qualitative approach. Research data were obtained from the transcription of dialogues in the film "Rudy Habibie" and were analyzed using linguistic analysis techniques to identify phonological and morphological interferences that occur. From the results of this research, it can be concluded that the movie "Rudy Habibie" contains interference at the phonological and morphological levels. This study provides a deeper understanding of language usage in the context of films and emphasizes the importance of adhering to language rules to ensure accuracy and authenticity in the use of language in literary works like films. Efforts to improve and develop more appropriate language usage in films can be a focus in enhancing the quality of films as cultural and communication media.